The Restless Wave : Good Times, Just Causes, Great Fights, and Other Appreciations - McCain, John and Salter, Mark (New York Simon & Schuster Publications, 2018)
"A candid new political memoir from Senator John McCain--his most personal book in years--covering everything from 2008 up to the present."--Provided by publisher.
Include Index
Keywords: McCain, John, -- 1936-2018. -- United States. -- Congress. -- Senate -- Biography. -- McCain, John, -- 1936-2018